International perspectives on spinal cord injury (WHO & ISCOS GenevaCH, 2013)
Documents the magnitude of and trends in spinal cord injuries (SCI), explores prevention strategies, analyses the situation of people with SCI around the globe, and gives examples of solutions across a range of economic settings that can enhance the lived experience of SCI.
Keywords: WOUNDS AND INJURIES